Structural change and the possibilities for future growth in Nigeria - Adeyinka, Adedeji; Salau, Sheu; Vollrath, Dietrich (International Food Policy Research Institute, 2017)
Since the turn of the century, overall economic growth in Nigeria has been consistently strong—averaging around 5.4 percent per year, up substantially from about 2.0 percent during 1990–2000. Moreover, overall GDP growth in the past decade is even higher if the oil sector—which accounts for 20–30 percent of GDP—is excluded, averaging around 8.4 percent per year, up sharply from 2.0 percent per year (Figure 5.1). This growth pickup has occurred alongside shifts in the composition of employment, mainly out of agriculture and into sectors such as manufacturing and finance and business services.